Students’ Perspectives on Popular Learning Platforms as Online English Assessment Tools - Muhammad, Fawwaz Al Falah; Setiawan, Slamet; Anam, Syafi’ul (Journal of English Teaching, Literature, and Applied Linguistics, 2025)
This study examined students’ perceptions of using popular online platforms for formative assessment in English teaching and learning. Employing a descriptive design with qualitative components, the research involved 68 English‐education undergraduates at the University of Muhammadiyah Gresik. Participants completed a questionnaire featuring Likert‐scale items to gauge their platform preferences and attitudes. Analysis revealed that 39 out of 68 students (57%) preferred Quizizz, 17 students (25%) favored Kahoot!, and 12 students (18%) opted for Booklet, Wordwall, and Mentimeter. Overall, respondents agreed that (1) these platforms feature engaging and user‐friendly interfaces, (2) they reduce opportunities for academic dishonesty, (3) Quizizz, in particular, fosters a competitive classroom environment, and (4) both Quizizz and Kahoot! are perceived as more effective than traditional offline tests. These findings suggest that integrating gamified online assessments can enhance student engagement, uphold assessment integrity, and potentially improve learning outcomes in English classrooms.